2012
DOI: 10.1002/j.2168-0159.2012.tb06009.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐35: Individual Differences in the Use of Binocular and Monocular Depth Cues in 3D‐Graphic Environments

Abstract: We found that 30 % of non-stereoanomalous observers, aged 19 to 25 years old, did not use disparity in making depth judgments in 3D-graphic environments. However, several questionnaires indicate that the use of disparity can be learned unconsciously, suggesting that poor stereopsis can be improved by appropriate training procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…It is also true that about 20% of the observers estimated the depth of the 3D-stimuli by using only binocular disparity. These ratios are similar to those reported by Fujisaki et al [4] in which the pictorial-cue group and the disparity group accounted for 30% and 20%, respectively. Thus, it is safe to say that the present study replicated the previous findings.…”
Section: Resultssupporting
confidence: 91%
“…It is also true that about 20% of the observers estimated the depth of the 3D-stimuli by using only binocular disparity. These ratios are similar to those reported by Fujisaki et al [4] in which the pictorial-cue group and the disparity group accounted for 30% and 20%, respectively. Thus, it is safe to say that the present study replicated the previous findings.…”
Section: Resultssupporting
confidence: 91%
“…The study yielded two main findings. First, the ratio of the pseudo‐stereoblind observers in the young group was roughly the same ratio as obtained in a previous study, strongly supporting the claim that a large number of young observers may have degraded depth percepts when viewing rich depth perception in current 3D graphic environments. Second, more than half of middle‐aged observers (40–54 years old) had trouble perceiving depth using disparity information; moreover, the percentage of pseudo‐stereoblind participants increased in older observers (55–83 years old), perhaps because of inadequate visual correction for age‐related visual deficits.…”
Section: Resultsmentioning
confidence: 99%
“…Individual differences in the availability of binocular disparity on viewing 3D graphics in various visual environments provide important information if the aim of society is to render 3D television accessible and popular for all age groups. Previous studies found that 17–30% of young and young‐middle people are pseudo‐stereoblind observers, meaning that they do not use disparity information when the depth of 3D graphic stimuli, which is presented for more than a few seconds, were evaluated by subjective judgments or a performance‐based task . This is the case even though these viewers can actually discriminate small levels of disparity in a Titmus stereoscopic test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudo-stereoanomaly is an altogether different phenomenon in which viewers with apparently normal stereo vision do not utilize the available stereopsis cues to improve performance on a given depth task (e.g., Kihara, Fujisaki, Ohtsuka, Miyao, Shimamura, Arai, & Taniguchi, 2013; Fujisaki, Yamashita, Kihara, & Ohtsuka, 2012). This appears to occur unconsciously and unintentionally to viewers, who do not seem to be aware of any problem.…”
Section: Stereoblindness Stereo-deficiency Stereo-anomaly and Pseumentioning
confidence: 98%